Photocatalytic treatment of organic and inorganic water pollutants using zinc phthalocyanine-cobalt ferrite magnetic nanoparticle conjugates - Mapukata, Sivuyisiwe (Rhodes University, Faculty of Science, Department of Chemistry, 2019)
This work explores the synthesis and photophysicochemical properties of zinc phthalocyanines when conjugated to cobalt ferrite magnetic nanoparticles. Phthalocyanines with amine and carboxylic acid functional groups were synthesised so as to covalently link them via amide bonds to cobalt ferrite magnetic nanoparticles with carboxylic acid and amine groups, respectively. Spectroscopic and microscopic studies confirmed the formation and purity of the phthalocyanine-cobalt ferrite magnetic nanoparticle conjugates which exhibited enhanced triplet and singlet quantum yields compared to the phthalocyanines alone. The studies showed that the presence of cobalt ferrite nanoparticles significantly lowered fluorescence quantum yields and lifetimes. The conjugates not only showed much higher singlet oxygen quantum yields compared to the phthalocyanines alone but were also attractive because of their magnetic regeneration and hence reusability properties, making them appealing for photocatalytic applications. The photocatalytic ability of some of the phthalocyanines and their conjugates were then tested based on their photooxidation and photoreduction abilities on Methyl Orange and hexavalent chromium, respectively. For catalyst support, some of the zinc phthalocyanines, cobalt ferrite magnetic nanoparticles and their respective conjugates were successfully incorporated into electrospun polystyrene and polyamide-6 fibers. Spectral characteristics of the functionalized electrospun fibers confirmed the incorporation of the photocatalysts and indicated that the phthalocyanines and their respective conjuagates remained intact with their integrity maintained within the polymeric fiber matrices. The photochemical properties of the complexes were equally maintained within the electrospun fibers hence they were applied in the photooxidation of azo dyes using Orange G and Methyl Orange as model organic compounds.
Keywords: Phthalocyanines; Cobalt ferrite; Zinc; Nanoparticles